ANALYSIS OF THE NEEDS OF ANIMATED VIDEO LEARNING MEDIA IN THE HUMAN ANATOMY AND PHYSIOLOGY COURSE IN THE SCIENCE STUDY PROGRAM AT UIN DATOKARAMA PALU - Pratiwi, Indri (Universitas Negeri Medan, 2025)
The purpose of this study was to analyze the learning media used during lectures in the Science Education Study Program in the Human Anatomy and Physiology course. This type of research is development research with the ADDIE development model at the Analyze stage. The population in this study were all Science Education students of UIN Datokarama Palu, and the study sample was used by 22 students who have taken courses in the Human Anatomy and Physiology. Data collection techniques through observation and filling out a needs questionnaire. The instrument used was a media needs questionnaire in the form of a questionnaire in the form of a google form. The data obtained were then analyzed descriptively qualitatively. The results of the study indicate that the learning process was mostly still conventional such as lectures and presentation discussions. The learning media used was also still limited to powerpoint and handouts. The Human Anatomy and Physiology course contains several concepts that cannot be learned directly but require the help of learning media such as animated videos to visualize abstract concepts including the digestive system material.